Business collaboration with universities as an example of corporate social responsibility - a review of case study collaboration methods - Gaweł, Aleksandra (Economics and Business Review, 2014)
Corporate social responsibility (CSR) is a concept which is gaining in popularity and is being included in the strategies of more and more companies. Social and environmental concerns, as well as cooperation with stakeholders which is also linked to the concept of sustainable development, are becoming part of the mission statements of numerous companies. The question arises, however, whether CSR is merely a strategic concept, or if it is accompanied by specific actions. The aim of this article is to answer the following questions: What does CSR really mean in hard economic times? Is cooperation between business and stakeholders just a declaration included in company strategies as an element of CSR, or is it an actual practice implemented in everyday activities? What barriers exist to such cooperation? The above issues will be discussed on the basis of the relationship between business and academia in respect of stakeholders and the social dimensions of CSR. The paper is divided into four sections. The first section describes the corporate social responsibility that relates to the economic, legal, ethical and philanthropic expectations which society has of companies, and which indicates the activities of companies which fulfil these stakeholder expectations. Universities are one of the business stakeholders within the social responsibility approach, an external and secondary stakeholder which is not critical to a company's survival. The second section discusses the case study method as a teaching method whereby collaboration between universities and busines is required to develop and apply this method during the educational process. University-business collaboration in this field gives an opportunity to fulfil the postulates of social responsibility through its impact on the quality of education. The next part of the paper analyses the case study of university- business collaboration in preparing case studies for educational purposes in Poland. Specific problems are discussed which indicate the constraints on collaboration between businesses and universities. The last section comprises conclusions and discussions. The main point of the discussion is that, on a declarative level, corporate social responsibility is a common element in companies' business strategies, but on an operational level collaboration with stakeholders as part of CSR does not easily transform into practical action. (original abstract)